2023
DOI: 10.1093/ecco-jcc/jjac190.0024
|View full text |Cite
|
Sign up to set email alerts
|

OP24 Neutralising antibody potency against SARS-CoV-2 wild-type and Omicron BA.1 and BA.4/5 variants in infliximab and vedolizumab treated patients with Inflammatory Bowel Disease after three doses of COVID-19 vaccine: a prospective multicentre cohort study

Abstract: Background Anti-tumour necrosis factor drugs such as infliximab are associated with attenuated antibody responses after COVID-19 vaccination. It is unknown how infliximab impacts vaccine-induced serological responses against highly transmissible Omicron variants, which possess the ability to evade host immunity and are now the dominating variants causing current waves of infection. Methods In this prospective, multicentre, ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Recent data from the CLARITY-IBD patient cohort reported a significantly higher rate of breakthrough infection with infliximab (13.7%) compared to vedolizumab (7%) in IBD patients who had received three vaccine doses. 99 101 This data argues that the lower response appreciated in IBD patients to the COVID-19 vaccines may be independent of immunomodulatory therapy; however, more studies are needed to confirm. 101 Additional booster doses may be of considerable benefit in patients on anti-TNF therapy.…”
Section: Vaccinationsmentioning
confidence: 93%
See 1 more Smart Citation
“…Recent data from the CLARITY-IBD patient cohort reported a significantly higher rate of breakthrough infection with infliximab (13.7%) compared to vedolizumab (7%) in IBD patients who had received three vaccine doses. 99 101 This data argues that the lower response appreciated in IBD patients to the COVID-19 vaccines may be independent of immunomodulatory therapy; however, more studies are needed to confirm. 101 Additional booster doses may be of considerable benefit in patients on anti-TNF therapy.…”
Section: Vaccinationsmentioning
confidence: 93%
“…Recent data from the CLARITY-IBD patient cohort reported a significantly higher rate of breakthrough infection with infliximab (13.7%) compared to vedolizumab (7%) in IBD patients who had received three vaccine doses. 99 Reassuringly, Spiera et al found that IBD patients who received at least two vaccine doses typically had milder disease courses from breakthrough SARS-CoV-2 infection with only 5.7% hospitalized, 3.4% with severe COVID-19, and 1.1% mortality. 100 In response to these studies, the Effectiveness and Safety of COVID-19 Vaccine in Patients with Inflammatory Bowel Disease Treated with Immunomodulatory or Biological Drugs performed a prospective, case-control study assessing humoral responses to COVID-19 vaccines in IBD patients across immunomodulatory therapies compared to healthy controls.…”
Section: Vaccinationsmentioning
confidence: 99%